2006
DOI: 10.1111/j.1365-2036.2006.03040.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the role of bile and pepsin in the pathophysiology and treatment of gastro‐oesophageal reflux disease

Abstract: SUMMARYGastro-oesophageal reflux disease is a multifaceted and multifactorial disorder which results from the reflux of gastric contents into the oesophagus. Animal studies suggest that synergism between acid and pepsin and conjugated bile acids have the greatest damaging potential for oesophageal mucosa, although unconjugated bile acids may be caustic at more neutral pH. Human studies are compatible with a synergistic action between acid and duodenogastric reflux in inducing lesions. During prolonged monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 76 publications
(85 reference statements)
2
35
0
1
Order By: Relevance
“…Bile reflux and volume reflux have been shown to provoke symptoms of ''heartburn'' [23][24][25]. Indeed studies have now been carried out using instruments that measure bile reflux as well as measuring volume reflux using Bilitec and impedance instruments [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Bile reflux and volume reflux have been shown to provoke symptoms of ''heartburn'' [23][24][25]. Indeed studies have now been carried out using instruments that measure bile reflux as well as measuring volume reflux using Bilitec and impedance instruments [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using combined pH and impedance monitoring in patients on PPI therapy that failed to provide symptom relief confirmed that, in up to one-third of patients, symptoms were associated with weakly acidic reflux events [18][19][20]. The nature of the stimulus that induces heartburn during weakly acidic reflux events has not been identified, but besides acid acting at pH above 4, bile is a potentially important contributor [21]. Esophageal perfusion with bile acids is able to induce a sensation of heartburn [22], and bile reflux has previously been implicated in the pathogenesis of heartburn in patients with pernicious anemia [23].…”
Section: Introductionmentioning
confidence: 87%
“…As gastroesophageal reflux (GER)-derived bile aspiration has also been linked to lung infection, the effects of bile acids (BAs) on HIF-1 were studied. Clinical manifestations of GER disease, in particular, esophageal mucosal damage, are often attributed to BAs; however, evidence suggests that the pathophysiology of GER is far more complex (35). In order to ensure that the impact of bile on HIF-1 is due to a specific response rather than a general response, BAs were first tested for cytotoxicity toward the epithelial cell lines under investigation.…”
Section: Resultsmentioning
confidence: 99%